Alpha-1 Antitrypsin Deficiency in Canada: Regional Disparities in Diagnosis and Management. (14th May 2015) - Bradi, Ana C.; Audisho, Nadeen; Casey, Deborah K.; Chapman, Kenneth R.
Abstract: Background: Since 1999, as part of the Alpha1 International Registry (AIR), the Canadian Alpha-1 Antitrypsin Deficiency (AATD) Registry has maintained demographic and medical information volunteered by AATD individuals. Methods: We undertook a retrospective chart review to describe the characteristics of registry participants. Inclusion criteria were ZZ phenotype or other severe deficiency and written consent. We reviewed baseline medical records and annual follow-ups, conducted by mail. Results: The number of registrants ranged from 8.7 per million in British Columbia and Ontario to 1.3 per million in Quebec. Similarly, the rate of augmentation therapy use ranged from 7.7 per million in British Columbia to 0.1 per million in Quebec. 290 patients (146 males), most PiZZ, were enrolled by 2013. Patients with lung disease reported symptoms onset at (mean ± SD) 40 ± 11 years but were diagnosed as AATD at 47 ± 10 years. Typical patients were ex-smokers with respiratory symptoms, severely reduced FEV1, an accelerated rate of FEV1 decline, and minimal bronchodilator response. A subgroup diagnosed by liver disease or familial screening was younger and had better preserved lung function but a similar rate of FEV1 decline. There were 63 deaths, of which 29 were lung-related and 6 were liver-related. Average age at death was 60.5 ± 11.2 years. Discussion : Most patients experience a diagnostic delay of seven years after symptom onset, a period during which lung health may deteriorate further. There is marked regional variation in the rate of diagnosis and specific therapy usage for AAT in Canada.